EFFECT OF MCKENZIE METHOD WITH TENS ON LUMBAR RADICULOPATHY A RANDOMIZED CONTROLLED TRIAL (International Journal of Physiotherapy, 2016)
Background: Lumbar radiculopathy is a disease of the spinal nerve root generally accompanied by radicular pain in dermatomal distribution and/or neurologic symptoms. The previous studies were focusing on finding the disability and pain caused due to Lumbar Radiculopathy. This study is focusing on the disability, pain, range of motion of the spine and SLR. The objective of the study is to evaluate the effectiveness of Mckenzie method with TENS on reducing symptoms and disability of Lumbar radiculopathy.Methods: In the present prospective study patients with Lumbar radicular pain due to disc herniation or prolapse at level L4, L5 & S1 were randomized into two groups – Group A and Group B. the study included 40 patients, with 20 in each group. The selection criteria was based on the following - with age group 22-55years, both sexes – male and female, with radicular pain in L4, L5 & S1 dermatomes, disabling leg pain for 6-12 weeks duration, evidence of disc herniation confirmed on MR imaging. The radicular pain was measured using the SLR test, pain was measured using the VAS scale of 0 – 100, disability was measured using the MODI and Lumbar Spine ROM was measured using the MMST. Group-A were treated with McKenzie methods with TENS and Group-B were treated with general exercisewith TENS.Results: This study showed that there was a significant reduction of pain on the VAS, improvement in SLR, lumbar spine range of motion using MMST and disability using MODI for both the groups. The statistical analysis found that experimental group showed earlier control of all the outcome measures when compared to controlled group at the end of the 6th week.Conclusion: After 6 weeks of Mckenzie method with TENS intervention for 30 minutes for 5 days in week the statistical analysis concluded that the experimental group had significantly faster rates of reducing the symptoms of lumbar radiculopathy and reducing the disability due to lumbar radiculopathy.